Invocation of artificial intelligence in payroll - Kylämies, Jaakko (2020)
This master’s thesis studies invocation of artificial intelligence in payroll and how it could eventually improve firm’s performance. Artificial intelligence is coming or is already is in use on nearly all fields of life and payroll is no exception to this. Use of artificial intelligence is coming more and more topical also on the field of payroll. Artificial intelligence is very complex technology to take use and it effects to entire service process, so implementation of artificial intelligence must be observed also from strategic and service process perspectives. In this study service modularity is being used to clarify service process and which matters need to be taken into account when planning implementation of artificial intelligence. The study was done by using empirical methods and re-searching observations both on service provider and customer side. Study resulted findings which indicated that balance between customization and standardization has a key role in answering to diverse customer needs and standardizing process, so that service provider could centralize all the core parts of the process. Study also found out that firms should think carefully what the benefit of artificial intelligence is and how it will affect to the whole service process and where it should first be taken into use.